The Association of Provider and Practice Factors with HIV ART Adherence - MEYERS, David J. (AIDS, 2019)
OBJECTIVE: While Anti-Retroviral Therapy (ART) is essential to patients with HIV, there is substantial variation in adherence nationally. We assess how provider and practice factors contribute to successful HIV ART adherence. DESIGN: We used Medicaid Analytic Extract claims from 2008–2012. We attributed patients with HIV to the provider that provided the plurality of HIV-related services or primary care in a given year and assigned these providers to a medical practice based on the National Provider Identifier registry file. We fit successive linear hierarchical models with patient, provider, and practice characteristics to partition the variation in adherence driven by each factor. Our unit of analysis was the patient-year. SETTING: 14 US states with the highest HIV prevalence PARTICIPANTS: 111,013 patient-years representing 60,496 Medicaid enrollees living with HIV attributed to 4,930 providers and 1,960 practices MAIN OUTCOME MEASURE: Percent of year individual patients were adherent to an ART regimen RESULTS: Provider and practice random effects jointly explained 6.8% of variation in adherence with patient differences accounted for 45.2% of the variation. Patients seen by generalists and other specialists had a 1.6 (95%CI: 0.6–2.5) and 5.1 (95%CI: 4.1–6.1) percentage point greater adherence than those seen by infectious disease specialists (p<0.001). Every additional year a patient saw the same provider was associated with a 6% increase in adherence (95%CI:5.7–6.3). CONCLUSIONS: There is substantial variation in ART adherence attributable to providers and practices and between provider specialties. To improve ART adherence for patients living with HIV, structural aspects of care should be considered.